1998
DOI: 10.1046/j.1365-2591.1998.t01-1-00114.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sterilization on bending and torsional properties of K‐files manufactured with different metallic alloys

Abstract: The purpose of this study was to assess the effect of dry‐heat or autoclave sterilization on the resistance to fracture in torque and angular deflection and the resistance to bending of K‐type files made of nickel‐titanium (Nitiflex, Naviflex), titanium (Microtitane) or stainless steel (Flexofile, Flex‐R). Ten K‐type files of each sort, from size 25 to 40, were tested, according to ANSI/ADA specification 28 (1988) and ISO specification 3630 (1992). Sterilization with dry heat and autoclave slightly decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
0
12
1
1
Order By: Relevance
“…23 Nevertheless, repeated cycles of steam heat can damage dental instruments for corrosion 24 or deformation by alteration of mechanical properties. 25 Although our results did not show significant alterations on the surface of the mini-implants after four cycle of sterilization, Thierry et al 15 showed that autoclaving could modify the surface topography and chemical surface of NiTi alloys. Mattos et al 18 studied, in vitro, the effects of autoclave sterilization in fracture resistance of mini-implants and did not find differences on the mechanical properties.…”
Section: Discussioncontrasting
confidence: 65%
“…23 Nevertheless, repeated cycles of steam heat can damage dental instruments for corrosion 24 or deformation by alteration of mechanical properties. 25 Although our results did not show significant alterations on the surface of the mini-implants after four cycle of sterilization, Thierry et al 15 showed that autoclaving could modify the surface topography and chemical surface of NiTi alloys. Mattos et al 18 studied, in vitro, the effects of autoclave sterilization in fracture resistance of mini-implants and did not find differences on the mechanical properties.…”
Section: Discussioncontrasting
confidence: 65%
“…Overall, for the primary outcome, the meta-analysis is in favor of non-sterilized NiTi instruments (control). The studies that presented data with a statistically significant difference are: Silvaggio et al [18] in favor of the control and Canalda-Sahli [19] against the group subject to sterilization. Casper [10] is exactly at the center of the non-effect line, whereas the remaining three studies are unfavorable for the group subjected to heat sterilization even if their confidence intervals intercept the non-effect line (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…For the second outcome, the forest plot is in favor of the subject group compared to the control. The studies that reported statistically significant data in favor of the experimental group are Silvaggio et al [17] and Canalda-Sahli et al 1998 [19], whereas those in favor of the control group are Casper et al 2011 [10] and King et al 2011 [9] (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…While conventional elevated-temperature heat treatment is not recommended for these instruments, they are subjected to sterilization procedures before being using again with a different patient. One study found that dry heat sterilization (180°C for 2 hours) and autoclave sterilization (220 kPa pressure and 136°C for 10 minutes) slightly decreased the flexibility and resistance to torsional fracture of the instruments but they still satisfied the requirements for minimum angular deflection in the ISO standard [50]. Further research is needed to gain insight into the metallurgical origins of the property changes.…”
Section: Stainless Steel Instrumentsmentioning
confidence: 99%